Evaluasi Kinerja dan Efektivitas CVT sebagai Sistem Transmisi pada Kendaraan Buggy 2WD - I Wayan Agus Rantia Dana; I Made Anom Adiaksa; I Wayan Suma Wibawa; I Made Bagus Panji Aditya (Journal of Applied Mechanical Engineering and Green Technology, 2026)
The development of non-conventional light vehicle technology, such as the buggy car, demands efficient and reliable power transfer systems to support mobility in congested industrial areas. One of the primary technologies utilized is the continuously variable transmission (cvt), which offers the advantage of changing transmission ratios continuously without the interruptions found in conventional gear shifting. However, in its application, an imbalance often occurs between the engine speed (rpm engine) and the wheel speed (rpm wheel) due to load factors and power losses. This study aims to comprehensively analyze the correlation between rpm engine and wheel performance on a buggy vehicle under varying loads ranging from 3 kg to 8 kg. Experimental results indicate that increasing the load leads to a significant decrease in wheel rpm across all engine speed ranges; for instance, at 8000 rpm engine, the wheel rpm dropped from approximately 515 rpm (3 kg load) to 225 rpm (8 kg load). Conversely, wheel torque exhibited a linear increase as the load rose, reaching a peak value of 15.8 nm at an 8 kg load. effectiveness analysis shows that the output power (hp) tends to increase with the load, with the highest effectiveness achieved during lower engine speed operations (5500 rpm) at peak load. These findings provide a scientific contribution to understanding the mechanical behavior of cvts and serve as a technical reference for optimizing transmission tuning in light vehicles to achieve a balance between torque and power efficiency.